2011
DOI: 10.1103/physreve.84.056320
|View full text |Cite
|
Sign up to set email alerts
|

Rotating electro-osmotic flow over a plate or between two plates

Abstract: In this paper, we investigate rotating electro-osmotic (EO) flow over an infinite plate or in a channel formed by two parallel plates. The analysis is based on the Debye-Hückel approximation for charge distributions and the Navier-Stokes equation for a transport electrolyte in the rotating frame. It is shown that, for the single plate, the nondimensional speed of system rotation ω is the singly most important parameter, while for the channel, in addition to ω, the nondimensional electrokinetic width K also pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 10 publications
9
43
0
Order By: Relevance
“…It is important to mention in this context that these values fall within the standard permissible limit. 32,34,35 It is seen from the Figs. 2(a)-(b) that the electroosmotic forcing which essentially acts in the zone close to the walls, drives the fluid close to the walls at small times…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…It is important to mention in this context that these values fall within the standard permissible limit. 32,34,35 It is seen from the Figs. 2(a)-(b) that the electroosmotic forcing which essentially acts in the zone close to the walls, drives the fluid close to the walls at small times…”
mentioning
confidence: 82%
“…(26)- (27) was found by Gheshlaghi et al 15 and steady state solution was found by Chang and Wang. 32 Here, we progress to find analytical solution for Eqs. (26)- (27) and also for a special case of Newtonian fluid we validate our solution with Gheshlaghi et al 15 We would like to mention here that, hereon, we drop the superscript '*' in the equations and boundary conditions for ease of presentation and symbols without superscript '*' represent the dimensionless quantities.…”
Section: Non-dimensionalization Of the Transport Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rotating coordinate system, the continuity equation and Navier-Stokes equation can be expressed by (Chang and Wang, 2011)…”
Section: Uniform Electric and Magnetic Fields (Case I)mentioning
confidence: 99%
“…In addition, there are several literatures associated with the effect of uniform rotation on the electrohydrodynamic instability (Takashima, 1976;Othman, 2004;Ruo et al, 2010). Chang and Wang (2011) developed a steady rotating electro-osmotic flow through microparallel plates. They obtained analytical solutions of rotating electroosmotic velocity field and volume flow rate.…”
Section: Introductionmentioning
confidence: 99%